Magnesium electrode surface machining method based on femtosecond laser

The magnesium electrode surface is processed by femtosecond laser to generate a periodic micro-nano strip structure, which solves the problem of poor discharge performance of magnesium air batteries and achieves the effect of improving discharge voltage and energy density.

CN119407482AActive Publication Date: 2025-02-11BEIJING UNIV OF TECH
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202411553529.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-02
Publication Date
2025-02-11
Estimated Expiration
2044-11-02

AI Technical Summary

Technical Problem

The actual discharge performance of magnesium air batteries is far from the theoretical value. It is mainly due to the active chemical properties of magnesium and poor corrosion resistance, which leads to uneven dissolution of magnesium negative electrode and self-corrosion hydrogen analysis reaction, which reduces the utilization efficiency and discharge voltage of the negative electrode.

Method used

The magnesium electrode surface processing method based on femtosecond laser is adopted to generate a periodic micro-nano bar structure through femtosecond laser processing, which improves the active contact area and electrochemical performance of the magnesium negative electrode.

Benefits of technology

It significantly improves the discharge voltage and energy density of magnesium air batteries, maintains the utilization efficiency of the negative electrode, reduces the solid-liquid interface resistance, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005115732450000011
    Figure HDA0005115732450000011
  • Figure HDA0005115732450000012
    Figure HDA0005115732450000012
  • Figure HDA0005115732450000021
    Figure HDA0005115732450000021
Patent Text Reader

Abstract

The invention discloses a magnesium electrode surface processing method based on femtosecond laser, and belongs to the technical field of battery material processing. According to the technical scheme, the method comprises the following steps that (1) magnesium alloy surface pretreatment is conducted, specifically, step-by-step grinding, polishing and cleaning are conducted, so that a mirror face is formed to serve as a machining face; (2) preparing a micro-nano structure layer in situ through femtosecond laser, and adjusting processing parameters and a scanning strategy to form a periodic microstructure; and (3) cleaning and drying, and storing in vacuum or inert gas. The method is simple in process, a micro-nano-size periodic structure layer can be generated on the surface of the crystalline magnesium alloy in situ, spreading of electrolyte on the surface of an electrode is remarkably promoted, the effective contact area of a solid / liquid interface is increased, and electrochemical reaction is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a femtosecond laser-based magnesium alloy electrode surface processing method, belonging to the technical field of battery material processing. Background Art

[0002] Magnesium-air batteries have great application potential and have received widespread attention in recent years. Magnesium metal raw materials are widely available and have low costs. Magnesium is one of the few advantageous metal resources in my country, with total reserves accounting for 22.5% of the world's total reserves; magnesium has a low density and has a higher theoretical voltage (3.1V), theoretical specific capacity (2200mAh / g) and theoretical energy density (6.8kWh / kg) compared to other air batteries that have been studied more, such as lithium and aluminum; magnesium-air batteries usually use inorganic salt solutions such as neutral sodium chloride as electrolytes, which are not only easy to obtain, but also can effectively avoid the harm of corrosive organic solutions and alkaline solutions to the body. Therefore, magnesium-air batteries have become a research hotspot for new energy storage technologies.

[0003] The theoretical discharge voltage and energy density of magnesium-air batteries are relatively high, but the performance indicators achieved during actual operation are far from the theoretical values. The main reasons for this phenomenon are: (1) The chemical properties of magnesium are active and its corrosion resistance is poor, which makes magnesium prone to corrosion reactions in aqueous electrolytes. The uneven dissolution of the magnesium negative electrode during the discharge process causes the unreacted matrix to fall off the electrode surface, resulting in a "block effect" and reducing the utilization efficiency of the negative electrode; (2) As a side reaction of the magnesium discharge process, the self-corrosion hydrogen evolution reaction consumes additional active substances, further reducing the utilization efficiency of the magnesium negative electrode. In addition, the products of the magnesium discharge process are easily attached to the electrode surface, reducing the active surface area of ​​the magnesium negative electrode in contact with the electrolyte.

[0004] In order to reduce the self-corrosion hydrogen evolution rate of magnesium negative electrode and improve the discharge performance of magnesium-air batteries, a large number of studies are currently focused on regulating the microstructure through alloying, plastic deformation or heat treatment. However, in the research of magnesium negative electrodes, there has long been a contradiction between discharge activity and utilization efficiency: in order to improve the utilization efficiency of the negative electrode, the electrochemical activity of magnesium alloys in aqueous electrolytes must be reduced to enhance corrosion resistance, but this will lead to a decrease in discharge voltage, thereby limiting the improvement of battery energy density.

[0005] The electrode structure has a great influence on the electrochemical properties and discharge performance of metals and their alloys. Recent studies have found that the preparation of magnesium negative electrodes with different surface nanostructures, such as microspheres, microsheets, nanorods and sea urchins, can achieve battery performance superior to that of commercial magnesium. Using magnesium alloys with good corrosion resistance as the substrate, constructing micro / nano structures, and expanding two-dimensional planar electrodes to more dimensions is expected to effectively increase the contact area between the electrode and the electrolyte, reduce polarization and contact resistance, and increase the battery discharge voltage while maintaining the utilization efficiency of the negative electrode, thereby increasing the energy density of the battery. However, the current methods for constructing electrode microstructures mostly use chemical preparation, in-situ growth, electrodeposition and other methods, most of which are relatively complex, have harsh conditions, and have a great influence on the bulk grain composition.

[0006] In view of this, we propose the present invention. Summary of the invention

[0007] The present invention aims to overcome the deficiencies of the prior art and to provide a femtosecond laser-based magnesium electrode surface processing method.

[0008] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0009] A femtosecond laser-based magnesium electrode surface processing method, characterized in that the preparation method specifically comprises the following steps:

[0010] (1) Select magnesium or magnesium alloy and obtain a sample of the required size by wire cutting;

[0011] (2) Grind the machined surface of the specimen step by step with sandpaper and polish it until the machined surface is mirror-like;

[0012] (3) placing the sample on the sample stage of a femtosecond laser device, keeping the processing surface facing upward, and performing femtosecond laser processing; (4) rinsing the processed sample with ethanol, drying it, and storing it in a vacuum or inert atmosphere.

[0013] The magnesium alloy has alloy elements selected from the group consisting of Sn, Ca, Al, Zn, Mn, rare earth and the like, and the total mass fraction of the alloy elements does not exceed 20%.

[0014] The magnesium alloy is a cast alloy or an alloy that has been subjected to heat treatment and plastic deformation.

[0015] The magnesium alloy processing surface is ground with sandpaper of a certain mesh size from low to high, and the highest mesh size is 5000, and then polished to a mirror surface.

[0016] The femtosecond laser processing is performed in an environment of air or ethanol.

[0017] The femtosecond laser processing has a laser pulse repetition frequency range of 500 Hz to 2 kHz, a central wavelength range of 400 nm to 900 nm, a pulse width of less than 50 fs, and a power range of 10 mW to 20 W.

[0018] The focus spot of the femtosecond laser processing is circular or linear, the diameter of the circular spot is in the range of 1 μm to 5 mm, and the width of the linear spot is in the range of 10 μm to 5 mm.

[0019] In the femtosecond laser processing, the angle between the incident angle and the electrode surface is in the range of 10° to 90°.

[0020] The femtosecond laser processing has a laser processing scanning speed range of 0.01 mm / s to 1 cm / s and a scanning interval range of 0.005 mm to 1 mm.

[0021] The femtosecond laser processing has a scanning path of concentric circle filling scanning, zigzag filling scanning and bow-shaped filling scanning.

[0022] The femtosecond laser processing has a processing repetition frequency ranging from 1 to 20 times.

[0023] The ethanol flushing time does not exceed 10 seconds, the drying temperature is room temperature cold air, and the purging time does not exceed 20 seconds.

[0024] The inert atmosphere is high purity N 2 or Ar.

[0025] The surface through which the laser of the present invention passes has a periodic micro-nano strip structure.

[0026] The magnesium electrode obtained by the invention is directly used as the negative electrode of the magnesium-air battery.

[0027] The principles and advantages of the present invention are:

[0028] Femtosecond laser has the unique advantages of simple experimental conditions, high precision, good repeatability, and cold processing. It can accurately construct the surface structure without changing the microstructure characteristics of the bulk phase such as the grain size and the second phase, and maintain the advantages of the original bulk phase components. Through structural design and precise processing of magnesium electrodes, the active contact area of ​​the magnesium negative electrode participating in the discharge reaction can be effectively increased, the solid-liquid interface resistance can be reduced, and the discharge performance of magnesium-air batteries can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 These are photos of unprocessed AZ31 and Examples 1 and 2; from left to right are the unprocessed sample, Example 1, and Example 2, respectively.

[0030] Figure 2Surface morphology and element distribution diagram of unprocessed AZ31 and Examples 1 and 2, (a) unprocessed, (b) Example 1, (c) Example 2;

[0031] Figure 3 for Figure 2 Enlarged image of (c) and periodic micro-nanostructure.

[0032] Figure 4 The contact angles of unprocessed AZ31 and Examples 1 and 2 on 3.5 wt% NaCl aqueous solution, (a) unprocessed, (b) Example 1, (c) Example 2; (d) specific angle.

[0033] Figure 5 The discharge curves of unprocessed AZ31 and Examples 1 and 2 at different current densities (the electrolyte is 3.5 wt% NaCl aqueous solution, and the positive electrode is commercial MnO x / C);

[0034] Figure 6 Performance comparison of magnesium-air batteries of unprocessed AZ31 and Examples 1 and 2, (a) battery output voltage, (b) negative electrode utilization efficiency, (c) specific energy, (d) specific capacity

[0035] Figure 7 The unprocessed AZ31 and Examples 1 and 2 are at 10 mA / cm 2 Surface morphology of products after 2h of discharge, (a) unprocessed, (b) Example 1, (c) Example 2 DETAILED DESCRIPTION

[0036] The present invention is further described below in conjunction with specific embodiments. It should be noted that the following embodiments are only used to illustrate the specific implementation methods of the present invention and cannot limit the scope of protection of the present invention.

[0037] Embodiment 1:

[0038] A magnesium-air battery negative electrode material, the alloy grade of which is AZ31, and the actual component mass percentages detected by ICP are 3.14wt% Al, 0.98wt% Zn, and the rest Mg.

[0039] (1) Cutting the magnesium alloy into small cubes with a size of 10 mm × 10 mm and a thickness of 2 to 5 mm;

[0040] (2) The 10 mm × 10 mm front side was used as the processing surface and polished step by step to remove the oxide layer. The grits of the sandpaper were 240#, 800#, 1200#, 2000#, and 5000#, respectively, and polished to a mirror surface;

[0041] (3) Place the sample on the sample stage of the femtosecond laser equipment, keeping the processing surface facing upward; use a ×10 objective lens to focus the laser, set the femtosecond laser pulse repetition frequency to 1 kHz, the central wavelength to 800 nm, the processing power to 100 mW, the processing speed to 0.4 mm / s, the scanning interval to 0.5 mm, the spot shape to linear, the spot width to 1 mm, the "bow" shaped filling scan, and the number of repetitions to 1 time.

[0042] (4) Remove the sample from the processing table, rinse it with anhydrous ethanol for 3 seconds, blow it with cold air at room temperature for 5 seconds to make its surface completely dry, and store it in a vacuum before use.

[0043] Embodiment 2:

[0044] A magnesium-air battery negative electrode material, the alloy grade of which is AZ31, and the actual component mass percentages detected by ICP are 3.14wt% Al, 0.98wt% Zn, and the rest Mg.

[0045] (1) Cutting the magnesium alloy into small cubes with a size of 10 mm × 10 mm and a thickness of 2 to 5 mm;

[0046] (2) The 10 mm × 10 mm front side was used as the processing surface and polished step by step to remove the oxide layer. The grits of the sandpaper were 240#, 800#, 1200#, 2000#, and 5000#, respectively, and polished to a mirror surface;

[0047] (3) Place the sample on the sample stage of the femtosecond laser equipment, keeping the processing surface facing upward; use a ×10 objective lens to focus the laser, set the femtosecond laser pulse repetition frequency to 1 kHz, the central wavelength to 800 nm, the processing power to 100 mW, the processing speed to 0.6 mm / s, the scanning interval to 0.5 mm, the spot shape to linear, the spot width to 1 mm, the "bow" shaped filling scan, and the number of repetitions to 1 time.

[0048] (4) Remove the sample from the processing table, rinse it with anhydrous ethanol for 3 seconds, blow it with cold air at room temperature for 5 seconds to make its surface completely dry, and store it in a vacuum before use.

[0049] Depend on Figure 1 It can be seen that compared with the unprocessed samples, the surfaces of Example 1 and Example 2 are obviously no longer bright, indicating that the microstructure processing was successfully performed on the surface of the magnesium sheet.

[0050] Depend on Figure 2 It can be seen that the unprocessed AZ31 surface is flat, and micron-sized second phase particles are scattered on the surface; the surfaces of Examples 1 and 2, the matrix and the second phase all present a regular periodic structure, and the surface passed by the laser has a periodic micro-nano strip structure, and the width of the periodic structure is about 400nm (see Figure 3). It can be seen that femtosecond laser processing only changes the surface structure of the material, but does not change the shape and distribution of its second phase.

[0051] Depend on Figure 4 It can be seen that the contact angle of the unprocessed AZ31 to the 3.5wt% NaCl aqueous solution is about 95°, the contact angle of Example 1 is about 17°, and the contact angle of Example 2 is about 24°. Compared with the unprocessed AZ31, the contact angle of the laser-processed AZ31 is significantly reduced, showing an increase in lyophilicity. This reduced contact angle is conducive to promoting the spreading of the electrolyte on the electrode surface, increasing solid-liquid contact, and improving the battery discharge activity.

[0052] Depend on Figure 5 and Figure 6 As shown in (a), with 3.5wt% NaCl aqueous solution as the electrolyte, commercial MnO x / C is the positive electrode catalyst, unprocessed AZ31 and Examples 1 and 2 are the negative electrode materials to assemble the magnesium-air battery, and the discharge current is 1 mA / cm 2 When the unprocessed AZ31 battery has an average output voltage of 1.49V within 2h, the average output voltage of the battery assembled in Example 1 is 1.54V, and the average output voltage of the battery assembled in Example 2 is 1.56V. The discharge current is 10mA / cm 2 When the battery is assembled with unprocessed AZ31, Example 1 and Example 2, the average output voltage is 0.98V, 1.15V and 1.26V respectively. The discharge current is 20mA / cm 2 When the battery is assembled with unprocessed AZ31, Example 1 and Example 2, the average output voltage is 0.88V, 1.16V and 1.10V respectively. The discharge current is 50mA / cm 2 When the laser processed magnesium alloy is used, the average output voltage of the battery assembled with unprocessed AZ31, Example 1 and Example 2 is 0.54 V, 0.69 V and 0.72 V respectively. At the discharge current density tested, the discharge voltage of the laser processed magnesium alloy is significantly higher than that of the unprocessed alloy.

[0053] Depend on Figure 6 As can be seen in (b), the discharge current is 1mA / cm 2 When the battery is assembled with unprocessed AZ31, Example 1 and Example 2, the negative electrode utilization efficiency is 34.6%, 35.8% and 36.0% respectively; the discharge current is 10mA / cm 2 When the negative electrode utilization efficiency of unprocessed AZ31, Example 1 and Example 2 is 46.8%, 52.7% and 44.2% respectively; the discharge current is 20mA / cm 2When the negative electrode utilization efficiency of unprocessed AZ31, Example 1 and Example 2 is 49.7%, 52.3% and 49.5% respectively; the discharge current is 50mA / cm 2 When the negative electrode utilization efficiency of unprocessed AZ31, Example 1 and Example 2 is 58.2%, 56.0% and 53.9% respectively. Under the tested discharge current density, the negative electrode utilization efficiency of Example 1 and Example 2 is not significantly lower than that of the unprocessed sample. Figure 6 In (c), the discharge current is 1 mA / cm 2 When the discharge specific energy of the unprocessed AZ31, the battery assembled from Example 1 and Example 2 was 1153.8 mWh / g, 1248.1 mWh / g and 1268.0 mWh / g respectively, the discharge current was 10 mA / cm 2 When the discharge specific energy of the unprocessed AZ31, the battery assembled from Example 1 and Example 2 is 1025.2 mWh / g, 1283.3 mWh / g and 1298.5 mWh / g respectively, the discharge current is 20 mA / cm 2 When the discharge specific energy of the unprocessed AZ31, the battery assembled from Example 1 and Example 2 was 981.2 mWh / g, 1377.0 mWh / g and 1027.2 mWh / g respectively, the discharge current was 50 mA / cm 2 When the discharge specific energy of the battery assembled from unprocessed AZ31, Example 1, and Example 2 was 735.7 mWh / g, 790.5 mWh / g, and 851.7 mWh / g, respectively. The variation trend of the discharge specific capacity is consistent with the negative electrode utilization efficiency ( Figure 6 (d)). It can be seen that the present invention can significantly improve the discharge voltage and discharge specific energy of the magnesium-air battery while maintaining the negative electrode utilization efficiency and discharge specific capacity.

[0054] Depend on Figure 7 It can be seen that at 10mA / cm 2 After 2 hours of continuous discharge, compared with the unprocessed material, the discharge products of Examples 1 and 2 are obviously looser and have larger cracks on the surface. This structure is conducive to the electrolyte penetrating the product layer and contacting the magnesium matrix, thereby maintaining the continuous discharge and keeping the discharge voltage stable.

[0055] Although preferred implementation cases have been listed and described in detail herein, those skilled in the art will appreciate that various improvements, additions, substitutions, etc. may be made without departing from the spirit of the invention, and these contents are deemed to be within the scope of the invention as defined by the claims.

Claims

1. A femtosecond laser-based magnesium electrode surface processing method, characterized in that: The specific steps include: (1) Select magnesium or magnesium alloy and obtain a sample of the required size by wire cutting; (2) Grind the machined surface of the specimen step by step with sandpaper and polish it until the machined surface is mirror-like; (3) Place the sample on the sample stage of the femtosecond laser equipment, keep the processing surface facing upward, and perform femtosecond laser processing; (4) The processed samples are rinsed with ethanol, blown dry and stored in a vacuum or inert atmosphere.

2. The method according to claim 1, characterized in that The magnesium alloy comprises one or more alloying elements selected from the group consisting of Sn, Ca, Al, Zn, Mn, and rare earths, and the total mass fraction of the alloying elements does not exceed 20%; the magnesium alloy is a cast alloy or an alloy that has undergone heat treatment and plastic deformation; the machined surface of the magnesium alloy is polished with sandpaper having a grit ranging from low to high, with the highest grit being 5000, and then polished to a mirror finish.

3. The method according to claim 1, characterized in that The femtosecond laser processing has a processing environment in air or ethanol; the femtosecond laser processing has a laser pulse repetition frequency range of 500Hz to 2kHz, a central wavelength range of 400nm to 900nm, a pulse width of <50fs, and a power range of 10mW to 20W.

4. The method according to claim 1, characterized in that The focus spot of the femtosecond laser processing is circular or linear, the diameter of the circular spot is in the range of 1 μm to 5 mm, and the width of the linear spot is in the range of 10 μm to 5 mm.

5. The method according to claim 1, characterized in that The incident angle of the femtosecond laser processing and the angle between the electrode surface are in the range of 10° to 90°; the scanning speed of the femtosecond laser processing is in the range of 0.01 mm / s to 1 cm / s, and the scanning interval is in the range of 0.005 mm to 1 mm.

6. The method according to claim 1, characterized in that The scanning paths of the femtosecond laser processing are concentric circle filling scanning, zigzag filling scanning and bow-shaped filling scanning; the femtosecond laser processing has a processing repetition number ranging from 1 to 20 times.

7. The method according to claim 1, characterized in that The ethanol flushing time shall not exceed 10 seconds, the drying temperature shall be room temperature cold air, and the purging time shall not exceed 20 seconds; the inert atmosphere shall be high-purity N2 or Ar.

8. The method according to claim 1, characterized in that The surface through which the laser passes has a periodic micro-nano strip structure.

9. A magnesium electrode obtained by the method according to any one of claims 1 to 8 of the present invention.

10. Use of the magnesium electrode obtained by the method according to any one of claims 1 to 8 of the present invention directly as the negative electrode of a magnesium-air battery.

Citation Information

Patent Citations

  • Degradable implantable medical devices

    CN105030390A

  • Method for improving corrosion resistance of magnesium alloy surface through short-pulse laser

    CN107164711A

  • Magnesium alloy negative electrode and primary battery comprising same

    CN108615872A

  • Method for metal surface treatment through femtosecond laser

    CN109954966A

  • Method for enhancing corrosion resistance of magnesium alloy material

    CN114686894A